Bird atlas in action: using citizen science data to generate population trend alerts in Hessequa, South Africa - Daniel, Karis A.; Underhill, Les G.; van Rooyen, Johan A. (Frontiers in Bird Science, 2024)
Citizen science data are rapidly transforming the conservation landscape. Targeted participatory citizen science initiatives generate nuanced data capable of monitoring trends in populations and generating early warnings for species and habitats experiencing significant declines. In the Hessequa Atlasing Area, Western Cape, South Africa, citizen science 'atlasers' involved with the Second Southern African Bird Atlas Project (SABAP2) have worked with scientific leadership since 2014 to improve the quality of bird atlas data in their region for species monitoring. In this study, we used reporting rates from SABAP2 checklists in the Hessequa Atlasing Area to calculate changes in range size and relative abundance for the 165 most commonly reported species in the region. We used a seven-tier alert system and broad habitat categories to sort species by priority for conservation action. Our results showed that wetland and marine associated species are experiencing the greatest declines in range and relative abundance in the Hessequa Atlasing Area, whilst urban and grassland associated species are largely increasing. We discuss how observed changes in populations may be used to guide conservation action and provide recommendations for scientists and non-scientific community members on engaging with and responding to the changes highlighted in each of the seven alert levels provided.